Sol-Gel Synthesis and Structural Characterization of Nano-Thiamine Hydrochloride Structure. (10th September 2013) - Azimi, Salameh
Abstract : The study presents the synthesis of nano-thiamine hydrochloride structure (NTH) using sol-gel method by hydrolysis of tetraethyl orthosilicate with ethanol and water mixture as silica source and nitric acid as catalyst support in which thiamine hydrochloride nanocrystals were dispersed in the silica glassy matrix. The synthesized nanocomposite was characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and differential thermal analysis (DTA). The morphological observation of the SEM results reveals that the nano-thiamine hydrochloride composites are in the range of 5–15 nm in size.